Primary Pure Squamous Cell Carcinoma of Kidney Associated with Multiple Stag Horn Stones - Hosseinzadeh, Massood (Int Med Case Rep J, 2020)
Primary Squamous cell carcinoma (SCC) of the kidney is rarely reported in the literature. It is usually associated with renal stone, and due to lack of clinical symptoms and radiological diagnostic features, patients often present at the late stages of the disease. We reported a 59-year-old woman presented with a longstanding history of flank pain and hematuria. Imaging techniques revealed enlargement of the right kidney associated with multiple staghorn stones. The patient subsequently underwent right radical nephrectomy, and histopathological examination of the mass revealed well-differentiated keratinized squamous cell carcinoma. There was no primary source for her SCC. Although the primary SCC of the kidney is a rare entity, it should be considered in patients with longstanding renal calculi, particularly for large staghorn stones of renal pelvis. On the other hand, conventional imaging could not detect this type of malignancy. In most cases, CT and MRI play an essential role in the diagnosis of such tumors.